PUASKAH PELANGGAN TOL TERHADAP TRANSAKSI NON TUNAI? (SURVEY PADA GERBANG TOL PASTEUR, PURBALEUNYI BANDUNG) - Mayasari, Indri (Politeknik Dharma Patria Kebumen, 2019)
This study aims to determine the effect of changing cash transactions to non-cash on customer satisfaction at the Pasteur Purbaleunyi Bandung Toll Gate. This research used descriptive quantitative method with 100 respondents. SPSS version 25 was used to analyze the data and Simple Linier Regression Test and Pearson Product Moment Correlationas the analysis technique. The result are value of t result> t table, that is 14,862 > 1,661. And the result of Adjust R Square analysis are value of R Square Coefficient are 0,693 or 69,3%. It?s mean that non cash transactions has a significant effect on customer satisfaction at Pasteur Toll Gate.